(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2025)
Background: The most common cause of death and disability in the world is stroke — which is a severe disruption of cerebral blood flow. We also see the biomarkers Troponin, Lactate Dehydrogenase (LDH), Creatine Kinase (CK), Hexokinase, and D-dimer used for stroke pathophysiology. Such biomarkers are associated with different disease parts, such as myocardial stress, cell damage, metabolic disturbance, and coagulopathy. Objective: This study aims to evaluate the correlation among Troponin, LDH, CK, Hexokinase, and D-Dimer levels in stroke patients to explore their clinical significance and potential as powerful diagnostic and prognostic tools. Methods: In a prospective study of 120 stroke patients, ischemic and hemorrhagic strokes. Blood was taken 24 hours after hospital admission for Troponin, LDH, CK, Hexokinase, and D-Dimer because of the beak of Troponin and other parameters will be reached after 24 hours from MI. The correlations of these biomarkers were calculated using Pearson correlation. Results: This is strong evidence of the positive correlations between all biomarkers that we found in our studies. Troponins correlated strongly with Lactate dehydrogenase LDH (r = 0.68, p 0.001), Creatin kinase CK (r = 0.71, p 0.001), and D-Dimer (r = 0.62, p 0.001) where r is statistically correlation-coefficient and p value is the probability. Similarly, LDH correlated strongly with CK (r = 0.75, p 0.001) and D-Dimer fragment of cross linked Fibrin D-Dimer (r = 0.65, p 0.001). Hexokinase was slightly inversely related to other biomarkers, suggesting an ischemic metabolic response. Conclusion: Because these biomarkers are significantly correlated, they may play an integrated role in stroke pathophysiology. Troponin, LDH, CK, Hexokinase, and D-Dimer might all be alternative markers for tissue injury, metabolic dysfunction, and coagulation abnormalities in stroke patients. This capability to be used in practice would go a long way toward improving stroke diagnosis and treatment, giving stroke patients a reason to feel confident in stroke care’s future.